Family Resilience in Preventing Child Deviance: Insights From Gayo Community Wisdom - Marlina, Marlina; Isnawati, Isnawati; Hidayat, Rahmat (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2024)
This study aims to describe the concept of a happy family in the Gayo tribe community with local wisdom values ​​in the form of family resilience in preventing children's deviant behavior. The research method used in this research is qualitative. Sources of data in the form of primary and secondary data sources. Data collection techniques using observation and interviews. After the data was collected, it was analyzed using qualitative data analysis with four stages, namely 1) data collection, 2) data condensation, 3) data display, and 4) conclusion drawing/verifying. The results of the study show that the concept of a happy family in Gayo society begins before marriage, each of them must know their partner, then after marriage, they must try to maintain family resilience. The pattern of family resilience in the Gayo community consists of physical and mental elements. Elements of birth include economic adequacy, education, availability of housing, and availability of transportation. While the Inner/Spiritual element is in the form of cultivating religious and customary values. Syariet berules, edet berules, agama kin senuwen, edet kin peger which means that Shari'a is carried out according to customary law, religion as the plant, custom as the fence.